Análise do polimorfismo t102c do receptor de serotonina (HTR2A) em pacientes com fibromialgia e controles - Alves, Fernanda Aparecida Vargas de Brito e (2012)
Introduction: Fibromyalgia is a syndrome characterized by widespread chronic pain. The syndrome is chronic with dubious possibility of healing. The prevalence in the world population varies from 0,66 to 4,4 %. It is believed that fibromyalgia is the result of abnormal changes in sensory processing of pain. In this context, are inserted gene polymorphisms T102C gene HTR2A serotonin receptor. The HTR2A gene T102C polymorphism is the presence of a thymine (T) or cytosine (C), defined by a transition from T to C at nucleotide position 102. It is a silent polymorphism receptor gene HTR2A, which determine the different levels of gene expression. Objectives: To determine and compare the allele frequency and genotype of the T102C polymorphism of the serotonin receptor gene HTR2A in a group of 48 women diagnosed with fibromyalgia and 50 healthy controls. Methodology: For this we used the PCR- RFLP , from DNA extracted from peripheral blood samples obtained from control and testing. The comparison of allele and genotype frequencies was performed by Chi -square test. Results: The results showed allele frequencies obtained for both groups were: T (46,9%) and C (53,1%). The TT genotype frequencies were found (22,9%), TC (47,9%) and CC (29,2%) for patients with fibromyalgia and TT (16%), TC (70%) and CC (14%) for controls. Conclusions: The FMS is composed of multiple characteristics that reflect a diversity of causes. Our results showed a significantly higher frequency for the CC genotype in patients with FMS, partially explaining the reduced serotoninergic response observed in such patients.